O poder da análise de dados das redes sociais no sucesso empresarial - MELO, Lucas Soares de (275, 2023)
MELO, Lucas Soares de. O poder da análise de dados das redes sociais no sucesso empresarial. S.P, 2023. Trabalho de conclusão de curso. (Curso superior de tecnologia em Gestão Comercial). Faculdade de Tecnologia de Assis, Prof. Dr. José Luiz Guimarães. Assis, 2023.

The process of analyzing data from social networks can guarantee important information for companies to increase the possibility of selling products. Knowing the facts, the work proposes to question whether the mass population is aware of how organizations act to collect this information. To help understand the theme, in addition to theoretical references, information from documentaries was also used, such as: “Network Dilemma” and “Hacked Privacy” all from Netflix. For data analysis, a case study of basic research with a qualitative approach was carried out using the Google form. The results showed that although a significant portion of respondents feel uncomfortable with data sharing, most of the people will not stop using social networks
The power of social media data analysis in business success
Keywords: Redes sociais; Informação; Gestão e Negócios